2012
DOI: 10.1371/journal.pone.0041204
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Functions of TonB-Dependent Transporters in Marine Bacteria and Environments: Implications for Dissolved Organic Matter Utilization

Abstract: BackgroundBacteria play critical roles in marine nutrient cycles by incorporating and redistributing dissolved organic matter (DOM) and inorganic nutrients in the ocean. TonB-dependent transporter (TBDT) proteins allow Gram-negative bacteria to take up scarce resources from nutrient-limiting environments as well as siderophores, heme, vitamin B12, and recently identified carbohydrates. Thus, the characterization of TBDT distribution and functions is essential to better understand the contribution TBDT to DOM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 71 publications
(110 reference statements)
6
97
0
Order By: Relevance
“…The TBDT family contains integral membrane proteins that use proton gradients, like the ones produced by PR, to transport molecules of different molecular weight across the outer bacterial membrane (reviewed by Tang et al, 2012). Their high expression supports previous results on the lifestyle of Flavobacteria as degraders of high molecular weight compounds (Cottrell and Kirchman, 2000;Cottrell et al, 2005;Teeling et al, 2012).…”
Section: Proton Motive Force (Pmf)-dependent Processessupporting
confidence: 74%
See 1 more Smart Citation
“…The TBDT family contains integral membrane proteins that use proton gradients, like the ones produced by PR, to transport molecules of different molecular weight across the outer bacterial membrane (reviewed by Tang et al, 2012). Their high expression supports previous results on the lifestyle of Flavobacteria as degraders of high molecular weight compounds (Cottrell and Kirchman, 2000;Cottrell et al, 2005;Teeling et al, 2012).…”
Section: Proton Motive Force (Pmf)-dependent Processessupporting
confidence: 74%
“…However, analysis of operons suggests that they might be involved in the uptake of polysaccharides, peptides, heme groups and/or vitamins. In our study, we observed two susC TBDT of particularly high expression in MED134 and DSW-1 T (MED134_12381 and MED134_05219) (Supplementary Table S2), which are possibly involved in the uptake of high molecular weight compounds such as proteins or complex carbohydrates (González et al, 2011;Tang et al, 2012).…”
Section: Proton Motive Force (Pmf)-dependent Processesmentioning
confidence: 68%
“…Bacteroidetes are particularly rich in carbohydrate-assimilation TBDT (Blanvillain et al, 2007;González et al, 2008;Hehemann et al, 2010;Tang et al, 2012) and biopolymer degradation enzymes (McBride et al, 2009;Hehemann et al, 2010;Qin et al, 2010;Thomas et al, 2012;Mann et al, 2013). Many Bacteroidetes glycoside hydrolase genes are organized in polysaccharide utilization loci, usually clustered with genes for TonB-dependent receptors, SusD-like proteins, sensors/transcription factors, transporters and frequently with genes for sulfatases (McBride et al, 2009;Hehemann et al, 2010;Qin et al, 2010;Thomas et al, 2012;Fernández-Gómez et al, 2013;Mann et al, 2013).…”
Section: Tonb-dependent Transportersmentioning
confidence: 99%
“…For example, studies in which commercially available organic compounds are added to seawater to evaluate effects on microbial diversity have become commonplace and, although they unfortunately yield little insight into how microbes consume DOM (e.g. , Nelson & Carlson 2012, Gómez-Consarnau et al 2012, they have been instrumental in constructing a paradigm regarding trophic strategies among different heterotrophic bacterioplankton (Tang et al 2012). The recent addition of gene and protein expression analyses to these experiments is providing a first glimpse at the physiology behind the consumption of specific DOM components (Vila-Costa et al 2010, Mou et al 2011, sources (Poretsky et al 2010, Rinta-Kanto et al 2011, Teeling et al 2012, and size fractions .…”
Section: An Interdisciplinary Approachmentioning
confidence: 99%
“…Organisms of the OM60 clade contain anywhere from 27 to 37 TBDT per genome, indicating that these types of transporters play a large role in complementing the nutritional requirements of the cell (Tang et al, 2012).…”
Section: Om60 Cladementioning
confidence: 99%